Well-being and internal resources during the COVID-19 pandemic in relation to meaning in life and existential anxiety - David Laura Teodora; Truța Camelia (Frontiers in Psychology, 2023)
The COVID-19 pandemic represents an event that placed humanity in a context where confrontation with uncertainty, isolation, life threats, and significant changes in one's life were on a scale that exceeded by far any previous individual or community crises. The interest of the present research was to investigate the relationship between meaning in life (MiL) and existential anxiety (EA) with personal internal resources such as creativity, playfulness, well-being, and personal meaning. A total of 451 participants from 48 countries (mean age 34.93 years, standard deviation 12.62, 31.9% men, 67.4% women) were questioned via online questionnaires between May and June 2020. Cluster analysis was performed on the meaning in life and existential anxiety that generated four categories of persons: Reactive, Superficial, Preoccupied, and Dedicated. Well-being and internal resources were associated mostly with the Dedicated type and less with the Reactive one. Arguments relying on the existential positive psychology suffering model and the hostile world scenario are presented to support the results and plead for interventions that elicit meaning, stimulate creativity, and guide people in finding purpose in order to ultimately promote psychological and mental health.
Keywords: meaning in life; existential anxiety; well-being; creativity; playfulness; COVID-1